Relationship Marketing, Product Diversity, and Trust: Their Impact on Reseller Loyalty at Trisna Shop Bali in Gianyar - Arimbawa, I Putu Eka; Sumerta, I Komang (Countable (Contemporary Business and Sustainability Science), 2024)
Consumer loyalty is one of the factors that determine the success of achieving company goals. Consumer loyalty is determined by various factors, including relationship marketing, product diversity and trust. Likewise at Trisna Shop Bali in Gianyar Regency, relationship marketing, product diversity and trust are factors that can affect reseller loyalty. The purpose of this study was to determine the simultaneous and partial effect of relationship marketing, product diversity and trust on reseller loyalty at Trisna Shop Bali in Gianyar Regency. Data collection techniques used by observation, interviews, questionnaire method (questionnaire) and study documentation. The number of samples taken in this study were 71 people with a sampling technique using accidental sampling. Furthermore, the data were analyzed using quantitative analysis consisting of the Classical Assumption Test, Multiple Linear Regression Analysis, Determination Analysis, Simultaneous Significance Test (Statistical F Test) and Individual Parameter Significance Test (Test Statistics t) with the help of the computer program IBM SPSS Statistic 25. The results of the analysis shows that there is a positive and significant influence simultaneously and partially between relationship marketing, product diversity and trust on reseller loyalty at Trisna Shop Bali in Gianyar Regency.